Quality Management of Indonesian Language Learning in Improving Students' Reading Literacy in Elementary Schools - Enur Nurhayati; Eva Dianawati Wasliman (Green Publisher Indonesia, 2026)
Reading literacy is a fundamental skill for elementary school students, serving as the foundation for mastering various fields of knowledge. However, students’ literacy skills still face challenges such as limited reading materials, lack of varied teaching methods, and an underdeveloped literacy culture. In this context, the quality management of Indonesian language learning plays a key role in ensuring effective and systematic teaching aligned with the Merdeka Curriculum. This study aims to analyze how quality management of Indonesian language learning supports the improvement of reading literacy at SDN Kertajadi and SDN Kiarangupuk, Cidaun District, Cianjur Regency. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation, and analyzed with Miles & Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings reveal that lesson planning referred to the Merdeka Curriculum but was limited by inadequate reading resources and less varied strategies. Learning implementation involved interactive approaches such as group discussions and text-based learning, yet literacy culture beyond the classroom remained weak. Evaluation used formative and summative assessments, but follow-up actions were not fully integrated into continuous improvement programs. The study concludes that quality management has contributed positively to students’ reading literacy but requires strengthening through sufficient resources, teacher training, and sustainable literacy programs involving the whole school community.